Using MALDI MS for rapid analysis of food lipids. Issue 11 (November 2015) - Shinn, Sara E.; Liyanage, Rohana; Lay, Jackson O.; Proctor, Andrew
Abstract : Matrix‐assisted laser desorption/ionization (MALDI) is an ionization method that produces intact lipid molecule species that can be separated and characterized by mass spectrometry. Recent research has concentrated on using rapid MALDI MS lipid analysis that employs little sample cleanup, simple sample preparation, no chemical derivatization, and minimal chromatography. This article takes a look at selected MALDI MS applications for edible oils and lipid rich foods, such as meat and eggs, and explores potential uses in food and lipid science.